2006
DOI: 10.1093/ije/dyl231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of education on overall and cause-specific mortality in injecting drug users, according to HIV and introduction of HAART

Abstract: Independently of HIV status, lower education predicts a higher risk of death in IDUs and its impact is stronger after 1997. Education has a protective effect on most causes of death and it cannot be entirely attributable to the access or use of HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
1
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 30 publications
2
24
1
2
Order By: Relevance
“…Similarly to some of these studies (Borrell et al, 2006;Jarrin et al, 2007;Saraceni et al, 2005) we found an inverse relationship between mortality and educational level, with differences so marked as a two-fold higher mortality in patients with none or basic education than in those with university degrees. However, these differences were not statistical significant, which may be attributed to the reduced number of adverse clinical outcomes observed in our series, clearly related to a relatively short follow-up period for patients receiving HAART.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Similarly to some of these studies (Borrell et al, 2006;Jarrin et al, 2007;Saraceni et al, 2005) we found an inverse relationship between mortality and educational level, with differences so marked as a two-fold higher mortality in patients with none or basic education than in those with university degrees. However, these differences were not statistical significant, which may be attributed to the reduced number of adverse clinical outcomes observed in our series, clearly related to a relatively short follow-up period for patients receiving HAART.…”
Section: Discussionsupporting
confidence: 89%
“…Limitations to our study include a relatively short follow-up period for evaluating clinical outcomes, although the results we found after one year of follow-up fully agreed with those of other studies (Borrell et al, 2006;Jarrin et al, 2007;Saraceni et al, 2005). On the other hand, other newer, potent antiretroviral regimens might obtain better clinical or viroimmunological outcomes.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations